Surveillance quality correlates with surgical site infection rates in knee and hip arthroplasty and colorectal surgeries: A call to action to adjust reporting of SSI rates. (18th December 2021) - Atkinson, Andrew; Eisenring, Marie-Christine; Troillet, Nicolas; Kuster, Stefan P.; Widmer, Andreas; Zwahlen, Marcel; Marschall, Jonas
Abstract: Objective: The incidence of surgical site infections may be underreported if the data are not routinely validated for accuracy. Our goal was to investigate the communicated SSI rate from a large network of Swiss hospitals compared with the results from on-site surveillance quality audits. Design: Retrospective cohort study. Patients: In total, 81, 957 knee and hip prosthetic arthroplasties from 125 hospitals and 33, 315 colorectal surgeries from 110 hospitals were included in the study. Methods: Hospitals had at least 2 external audits to assess the surveillance quality. The 50-point standardized score per audit summarizes quantitative and qualitative information from both structured interviews and a random selection of patient records. We calculated the mean National Healthcare Safety Network (NHSN) risk index adjusted infection rates in both surgery groups. Results: The median NHSN adjusted infection rate per hospital was 1.0% (interquartile range [IQR], 0.6%–1.5%) with median audit score of 37 (IQR, 33–42) for knee and hip arthroplasty, and 12.7% (IQR, 9.0%–16.6%), with median audit score 38 (IQR, 35–42) for colorectal surgeries. We observed a wide range of SSI rates and surveillance quality, with discernible clustering for public and private hospitals, and both lower infection rates and audit scores for private hospitals. Infection rates increased with audit scores for knee and hip arthroplasty ( P value for the slope = .002), and this was also the case for planned ( P = .002), and unplanned ( P = .02) colorectal surgeries. Conclusions: Surveillance systems without routine evaluation of validity may underestimate the true incidence of SSIs. Audit quality should be taken into account when interpreting SSI rates, perhaps by adjusting infection rates for those hospitals with lower audit scores.